2-X=6                                                                                                                                   9-X=4                                                                                                                                   X-8=1                                                                                                                                  X+5=9

    9-X=4  
    -х=4-9
    -х= -5
    х=5
                                                                  

  • первое= -4
    второе =5
    третье =9
    шестое =4
  • 2-X=6    
    -х=6-2
    -х=4
    х= -4

                                                            
                                                          X+5=9
    х=9-5
    х=4

  •     
    х=1+8
    х=9
                                                                                
                                                                        
                                                                   X-8=1   


See also: